Phosphate adsorption on metal oxides and metal hydroxides: A comparative review - Li, Mengxue; Liu, Jianyong; Xu, Yunfeng; Qian, Guangren (Environmental reviews, 2016)
Phosphorus removal from wastewater is important for eutrophication control of water bodies. Metal oxides and metal hydroxides have always been developed and investigated for phosphorus removal, because of their abundance, low cost, environmental friendliness, and chemically stability. This paper presents a comparative review of the literature on the preparation methods, adsorption behaviors, adsorption mechanisms, and the regeneration of metal (hydr)oxides (e.g., Fe, Zn, Al, etc.) with regard to phosphate removal. The contrasting results showed that metal hydroxides could offer an effective and economic alternative to metal oxides, because of their cost–benefit synthesis methods, higher adsorption capacities, and shorter adsorption equilibrium times. However, the specific surface area of metal oxides is larger than that of metal hydroxides because of the calcination process. Metal oxides with a higher pH at the zero point of charge have wider optimal adsorption pH ranges than metal hydroxides because of their surface precipitation in alkaline solutions. The regeneration of metal oxides using acids, bases, and salts and that of metal hydroxides using acids and bases has been critically examined. Further research on uniform metal (hydr)oxides with small particle size, high stabilities, low cost, and that are easily regenerated with promising desorbents are proposed. In addition, quantitative mechanism study and application in continuous-mode column trials are also suggested.